(untitled) (Constructionism Conference Proceedings, 2025)
Constructionist education, based on its fundamental premises, has consistently proven effective in fostering a more holistic and integrative education. These premises align with the aspirations of formal education, which is monitored and evaluated through external and standardized assessments that do not always capture such comprehensive development. Drawing upon the tenets of constructionism, we hypothesize that pedagogical practices grounded in Creative Learning (CL), an outgrowth of constructionism, have the potential to directly impact student learning and performance, and that this impact can be captured by assessments. Consequently, we acknowledge that for such success, the formative process must be linked to the development of teaching practice that aligns with the desired transformative ideal, moving away from reproducing a traditional and passive education that is misaligned with the aspired protagonistic stance. Thus, this study investigated the impact of teacher training grounded in CL principles on pedagogical practice and student reading and writing performance. This exploratory research was conducted in two phases. The first phase (2023) involved direct monitoring and intervention with 14 teachers, 16 classes, and 377 students from one school district, divided into a control group (CG) and an intervention group (IG). The second phase (2024) focused on the potential for scaling up and replication, with a sample of 3 school districts, 101 teachers/classes, and 2600 students, and included a cascading formative layer. The results showed significant gains in phase 1 and promising results in phase 2 (currently under analysis), confirming the direct relationship between a constructionist formative approach, the transformation of teaching practice, academic performance, and holistic education.